Learning to Play: Cognitive and Physical Development of Children and the Requirements of Playing the Piano - Amy Carmichael (Musical Offerings, 2014)
Musical learning and performance has traditionally been understood as the process of cognitive ability and physical action. If a musician lacks or is underdeveloped in one of these areas it will either be harder or almost impossible to create music. In this presentation I will focus on the connection between them. Cognitive ability and knowledge increases with age as we gain more facts and experiences. Likewise, a child’s physical abilities expand and become more advanced with age. There is an increasing amount of evidence that cognitive abilities and physical developments are linked in children’s development.